2011
DOI: 10.1002/hep.24192
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of lamivudine versus entecavir in entecavir-treated patients with undetectable hepatitis B virus DNA: Outcome at 2 Years

Abstract: We aimed to determine the 2-year outcomes of entecavir followed by lamivudine in patients with undetectable viral load (<12 IU/mL) and normal alanine aminotransferase (ALT) after initial entecavir treatment for at least 6 months. Patients were randomly assigned 1:1 to continue with entecavir or switch to lamivudine. Liver biochemistry and hepatitis B virus (HBV) DNA were determined at weeks 0, 4, 12, 24, 48, 72, and 96. Mutational analysis using line-probe assay were performed at weeks 0, 24, 48, and 96 and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…This rate of virologic breakthrough (23.4%) during the 48-week telbivudine therapy in this study was comparable to that in a previous trial, which showed a 28.8% virologic breakthrough during a 2-year telbivudine treatment regimen in patients who were HBeAg-positive [19]. This observed rate is also similar to the rate of virologic rebound (24%) observed during lamivudine treatment in patients who had achieved undetectable serum HBV DNA following the preceding entecavir treatment [27]. …”
Section: Discussionsupporting
confidence: 87%
“…This rate of virologic breakthrough (23.4%) during the 48-week telbivudine therapy in this study was comparable to that in a previous trial, which showed a 28.8% virologic breakthrough during a 2-year telbivudine treatment regimen in patients who were HBeAg-positive [19]. This observed rate is also similar to the rate of virologic rebound (24%) observed during lamivudine treatment in patients who had achieved undetectable serum HBV DNA following the preceding entecavir treatment [27]. …”
Section: Discussionsupporting
confidence: 87%
“…Previously published research has focused on the comparative clinical effectiveness [18][19][20][21][22][23] and/or costeffectiveness 24-28 of oral antiviral agents in the treatment of CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Fung, et al5 started treating patients with HBV DNA loss with ETV and then switched to lamivudine and continued the treatment for 2 years. The study was based on an earlier study that reported a low incidence of resistance in the first 2 years of lamivudine treatment in patients with serum HBV DNA that was undetectable with PCR (<300 copies/mL) at week 24 of lamivudine treatment 7.…”
Section: Discussionmentioning
confidence: 99%
“…Viral reemergence was observed in 6 of 25 patients (24%), and resistance was found in 3. Therefore, Fung, et al5 expressed negative views toward lamivudine-switching therapy in patients with a favorable response to ETV therapy. However, they also reported that, after rebound, 3 patients were again treated with ETV to induce HBV DNA loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation